The king's three faces : the rise & fall of royal America, 1688-1776 - McConville, Brendan, 1962- (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, by the University of North Carolina Press, 2006)
Reinterpreting the first century of American history, Brendan McConville argues that colonial society developed a political culture marked by strong attachment to Great Britain's monarchs. This intense allegiance continued almost until the moment of independence, an event defined by an emotional break with the king. The American Revolution, McConville contends, emerged out of the fissure caused by the unstable mix of affective attachments to the king and a weak imperial government.